ITGB1-mediated molecular landscape and cuproptosis phenotype induced the worse prognosis in diffuse gastric cancer - Zhu, Xingyu; Chen, Hao; Li, Han; Ren, Huicheng; Ye, Chunshui; Xu, Kang; Liu, Jin; Du, Fengying; Zhang, Zihao; Liu, Yuan; Xie, Xiaozhou; Wang, Mingfei; et al. (Frontiers in Oncology, 2023)
Diffuse type gastric cancer was identified with relatively worse prognosis than other Lauren’s histological classification. Integrin β1 (ITGB1) was a member of integrin family which played a markedly important role in tumorigenesis and progression. However, the association between ITGB1 and diffuse gastric cancer (DGC) remains uncertain. Here, we leveraged the transcriptomic and proteomic data to explore the association between ITGB1 expression and clinicopathologic information and biological process in DGC. Cell phenotype experiments combined with quantitative-PCR (q-PCR) and Western-blot were utilized to identify the potential molecular mechanism underling ITGB1.Transcriptomics and proteomics both revealed that the higher ITGB1 expression was significantly associated with worse prognosis in DGC, but not in intestinal GC. Genomic analysis indicated that the mutation frequency of significantly mutated genes of ARID1A and COL11A1, and mutational signatures of SBS6 and SBS15 were markedly increased in the ITGB1 low expression subgroup. The enrichment analysis revealed diverse pathways related to dysregulation of ITGB1 in DGC, especially in cell adhesion, proliferation, metabolism reprogramming, and immune regulation alterations. Elevated activities of kinase-ROCK1, PKACA/PRKACA and AKT1 were observed in the ITGB1 high-expression subgroup. The ssGSEA analysis also found that ITGB1 low-expression had a higher cuproptosis score and was negatively correlated with key regulators of cuproptosis, including FDX1, DLAT, and DLST. We further observed that the upregulated expression of mitochondrial tricarboxylic acid (TCA) cycle in the ITGB1 low-expression group. Reduced expression of ITGB1 inhibited the ability of cell proliferation and motility and also potentiated the cell sensitive to copper ionophores via Western-blot assay. Overall, this study revealed that ITGB1 was a protumorigenic gene and regulated tumor metabolism and cuproptosis in DGC.